BIOCHAR IMPROVES TOMATOES GROWTH CHALLENGED WITH KHOKHRAN VIRUS INFECTION - SHAKEEL, I; KHURSHID, M; MANZOOR, MT; ALI, S; AKHTAR, A; ANWAR, W; MUSHTAQ, Z; FAIQ, M; ABBAS, MT (Biological and Clinical Sciences Research Journal, 2024)
Tomato production in Pakistan is being seriously hampered by begomoviruses. To sustain tomato production and to contribute the growing economy of Pakistan, the researchers should focus on the innovative and organic disease prevention/management options. In this regard, the utilization of biochar as a soil amendment and to activate the defense mechanism of plants against invading pathogens emerged to be a reasonable solution. In this study, biochar produced from available organic waste through pyrolysis was used to tackle the begomovirus called the Khokhran virus. Various levels of biochar were applied alongside the soil. Five treatments were used, each involving the addition of biochar to soil: only soil with no biochar served as control, then treatments with 5 and 10% Green Biochar each, as well as 5 and 10% Wood Biochar amended soil substrate. According to the results of root and shoot mass, the treatment with 5%, Green Biochar yielded the best outcome. Plants grown with Green Biochar were taller and had higher yields compared to those in other treatments. Additionally, tests including PCR assays, RNA extraction, and DNA quantification were conducted to confirm the presence of viral load in each treatment. In conclusion, 5% Green Biochar was found to be most effective against the Khokhran virus, by boosting plant growth and inducing resistance.